2019
DOI: 10.3390/biom9110660
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Full-Length Human Dehydrodolichyl Diphosphate Synthase Using an Integrative Computational and Experimental Approach

Abstract: Dehydrodolichyl diphosphate synthase (DHDDS) is the catalytic subunit of the heteromeric human cis-prenyltransferase complex, synthesizing the glycosyl carrier precursor for N-linked protein glycosylation. Consistent with the important role of N-glycosylation in protein biogenesis, DHDDS mutations result in human diseases. Importantly, DHDDS encompasses a C-terminal region, which does not converge with any known conserved domains. Therefore, despite the clinical importance of DHDDS, our understating of its str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…SDS‐PAGE analysis of the complexes revealed the two protein components in roughly 1:1 ratio (Figure 3a). His‐tagged RWR78 alone expressed in S. cerevisiae and purified via Ni‐NTA resin and size‐exclusion chromatography was a homodimer (83.6 kDa) (Figure 3a), the same as the reported human DHDDS conformation (Lisnyansky et al, 2019) (we also confirmed that E. coli ‐expressed human DHDDS formed a homodimer as shown in Figure S4b). Besides, while using StrepTrap XT column and size‐exclusion chromatography to purify the S. cerevisiae ‐expressed sRWR71 or sRWR93, they formed a homodimer (67.3 and 61.4 kDa, respectively), similar to yeast Nus1 (Ma et al, 2019), but unlike the human sNgBR that forms a monomer (Holcomb et al, 2018).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…SDS‐PAGE analysis of the complexes revealed the two protein components in roughly 1:1 ratio (Figure 3a). His‐tagged RWR78 alone expressed in S. cerevisiae and purified via Ni‐NTA resin and size‐exclusion chromatography was a homodimer (83.6 kDa) (Figure 3a), the same as the reported human DHDDS conformation (Lisnyansky et al, 2019) (we also confirmed that E. coli ‐expressed human DHDDS formed a homodimer as shown in Figure S4b). Besides, while using StrepTrap XT column and size‐exclusion chromatography to purify the S. cerevisiae ‐expressed sRWR71 or sRWR93, they formed a homodimer (67.3 and 61.4 kDa, respectively), similar to yeast Nus1 (Ma et al, 2019), but unlike the human sNgBR that forms a monomer (Holcomb et al, 2018).…”
Section: Resultssupporting
confidence: 87%
“…Yeast Nus1, a NgBR homologue, forms a homodimer as revealed by its crystal structure (Ma et al, 2019). This Nus1 protein was modeled for binding with Rer2 to form a heterodimer (Lisnyansky et al, 2019), which is one of the two DHDDS‐like enzymes Rer2 and Srt1 in yeast (Shimizu et al, 1998), but the complexed structure and whether Nus1 could stimulate Rer2 activity were not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…While such speculations may turn out to be true, there is no direct empirical evidence extant to support this hypothesis. It is also entirely possible, however, that mutations (whether K42E or others) in DHDDS may affect its interactions with its enzymatic partner, Nogo-B receptor (NgBR, encoded by the Nus1 gene) [8,9], with concomitant alterations in dolichol synthesis and protein N-glycosylation [28,29]. At present, nothing is known about the expression of Nogo-B receptor or its interactions with DHDDS, specifically in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…DHDDS catalyzes cis-prenyl chain elongation in the synthesis of dolichyl diphosphate (Dol-PP), which is required for protein N-glycosylation [6,7]. DHDDS catalyzes the condensation of multiple units of isopentenyl pyrophosphate (IPP, also called isopentenyl diphosphate) 2 of 11 to farnesyl pyrophosphate (FPP, also called farnesyl diphosphate) to produce Dol-PP [8,9]. This is used as the "lipid carrier" onto which oligosaccharide chains are built that are ultimately transferred to specific asparagine (N) residues on nascent polypeptide chains in the lumen of the endoplasmic reticulum (ER) to form N-linked glycoproteins [10].…”
Section: Introductionmentioning
confidence: 99%